Associations of social network use and social network addictive behaviors with self-esteem in adolescents: the EHDLA study - Martínez-Iniesta, Estefanía; Montenegro-Espinosa, José Adrián; Bizzozero-Peroni, Bruno; Olivares-Arancibia, Jorge; Yáñez-Sepúlveda, Rodrigo; Duclos-Bastías, Daniel; Panisello Royo, Josefa María; Mesas, Arthur Eumann; López-Gil, José Francisco; Jiménez-López, Estela (Frontiers in Psychiatry, 2025)
ObjectiveThe aim of the present study was to examine the relationships of social network (SN) use and SN addictive behaviors with self-esteem in Spanish adolescents. The use of specific social media platforms and their associated addictive behaviors related to self-esteem were also evaluated.MethodsThis cross-sectional study used secondary data from the Eating Healthy and Daily Life Activities (EHDLA) project, which included a representative sample of adolescents aged 12–17 years from the Valle de Ricote in the Region of Murcia, Spain. The sample consisted of 632 adolescents. Addiction and SN use were assessed via the Short Social Media Addiction Scale, and self-esteem was assessed via the Rosenberg Self-Esteem Scale. Generalized linear regression analyses with Gaussian distributions were conducted to calculate unstandardized beta coefficients (B) and their 95% confidence intervals (CIs). Sociodemographic, lifestyle, and anthropometric data were included as covariates.ResultsIn terms of SN use, Instagram was the most accepted, in contrast to Facebook, which was the least used. The most notable addictive behaviors toward SN use included salience (i.e., when using SNs is the major concern and the priority motivation) and tolerance (i.e., when increasing use is desired). Furthermore, self-esteem levels decreased as adolescent’s addiction levels increased. In the adjusted model, an increase in each addictive behavior was associated with a significant decrease in self-esteem (B = -0.699; 95% CI -0.890 to -0.508; p < 0.001). Individually, there was a negative and significant association between Twitter use and self-esteem (B = -0.356; 95% CI -0.695 to -0.017; p = 0.040). With respect to addictive behaviors toward SNs, mood modification showed the strongest negative association with self-esteem (B = -2.580; 95% CI -3.192 to -1.968; p < 0.001), followed by conflict (B = -1.410; 95% CI -2.147 to -0.673; p < 0.001), relapse (B = -1.350; 95% CI -1.999 to -0.701; p < 0.001), tolerance (B = -0.928; 95% CI -1.596 to -0.260; p = 0.007), salience (B = -0.892; 95% CI -1.623 to -0.161; p = 0.017), and finally, withdrawal behaviors (B = -0.170; 95% CI -1.905 to -0.435; p = 0.002), all of which were significantly negatively associated with self-esteem in adolescents.ConclusionsSN use and SN addictive behaviors could significantly affect adolescent’s self-esteem. The findings suggest that the use of Twitter and certain addictive behaviors, such as tolerance, salience, mood modification, relapse, withdrawal, or conflict are particularly linked to lower self-esteem. These results highlight the need to develop strategies aimed at promoting healthy engagement with SN platforms and fostering adolescent’s psychological well-being.